Validitas E-LKPD Interaktif dalam Pembelajaran dengan Pendekatan PBL untuk Meningkatkan Kemampuan Berpikir Kritis - Evanti, Azizah Meilina Dhiah; Mawartiningsih, Lilik (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Learning tools play an important role in supporting the achievement of learning objectives. However, the use of printed textbooks in the learning process is still not optimal, and the student worksheets (LKPD) used do not fully meet the criteria for ideal worksheets. In addition, the current worksheets have not been designed to develop students' critical thinking skills. To address these problems, this study aims to develop an interactive E-LKPD based on a Problem Based Learning (PBL) approach that is valid and practical in improving critical thinking skills. This research is a development research by applying the 4D model consisting of four main stages, namely defining (defining), designing (designing), developing (developing), and disseminating (disseminating), although the dissemination stage was not implemented in this study. In the definition stage, an analysis of the characteristics and needs of students was conducted. The design stage includes designing the structure of the content and appearance of the E-LKPD, while the development stage includes a validity test by two expert lecturers and one science teacher. Based on the validation results from the experts, the interactive E-LKPD with a PBL approach obtained a validity assessment percentage of 91,2%, which is included in the highly valid category. Thus, it can be concluded that the developed interactive e-LKPD has proven to be highly valid and practical for use as an innovative learning medium that supports students' critical thinking skills.